Heaven & earth - Stone, Oliver; Milchan, Arnon; Kline, Robert; Ho, A. Kitman; Le, Thi Hiep; Jones, Tommy Lee 1946-; Chen, Joan; Ngor, Haing S.; Hayslip, Le Ly; Hayslip, Le Ly (Warner Bros., 1993)
The true story of Phung Thi Le Ly Hayslip who emigrated to the United States from Ky La, a rice-farming village in Central Vietnam near Da Nang. Beginning with the French destruction of her village in the early 1950's, Le Ly and her family suffer all the atrocities of war, until she meets an American soldier who takes her home to California. After overcoming culture shock and a troubled marriage, Le Ly achieves peace and security for herself and her children.